Implementasi Perlindungan Hak Pekerja terkait Kecelakaan Kerja oleh BPJS Ketenagakerjaan - Putri Rini Situmeang; Lia Ulvi Miranata Putri; Ayu Pebrianti (Lembaga Pengembangan Kinerja Dosen, 2023)
Occupational accidents are considered a risk that is difficult to avoid in production or work activities. Protection of rights can ensure the working life not to consider itself in a hazardous work environment, even if accidents at work are inevitable. The research uses implementation assessment elements: programs or policies, target groups, and implementers. The aim of this study is to find out how the implementation of worker rights protection is related to employment accidents at BPJS Employment. The research method used is qualitative, with a library study approach. As for the results obtained in this study, i.e. in creating social security related to work accidents as an attempt to protect workers or workers, the program or policy implemented is JKK (Work Accident Insurance) with the target group of workers and workers and implementers of the BPJS Employment. This research could draw the conclusion that the implementation of social security efforts related to work accidents is not optimal because there are still problems in these activities, such as delays, and companies do not do what should be done by the company.